COVID 19 related perceived discrimination in medical settings, March and April 2020 - Farzaneh Soleimani; Mahtab Aligholipour; Moosa Aghal; Ebrahim Aliafsari Mamaghani (SAGE Publishing, 2021)
Global spread of a disease causes fear that can lead to discrimination against the people infected with the disease. On December 2019, COVID-19 emerged in Wuhan, China, and has spread throughout the world. In this descriptive and analytic study Perceived discrimination of the patients admitted to COVID-19 wards was measured in medical settings. Data was collected of 176 patients discharged in March and April 2020. Discrimination scale was used to collect data in medical settings. Overall mean score of the scale was 11.51 ± 3.883 indicating low level of perceived discrimination. The highest level of discrimination belonged to refusal of physicians and nurses to physically examine the patients (0.992 ± 3.49). Low level of perceived discrimination was reported in this study, which necessitated taking useful measures to identify discrimination, determines causes and prevent discriminatory behaviors in medical settings to improve the hospitalization experience and disease outcomes.